(untitled) (GYMNASIUM, 2017)
When googling motivation + learning, you will get in less than one second 185.000.000 results. It is obvious that we do not lack information about what is motivation and how it is related to learning. How is it then possible, that at the same time even 60% of students think teaching they are participating is boring at least half of the time? We claim that it is much easier to tell in theory what is interesting or how to build motivation, than to do it in practice. Since 2011, we have been developing tools for inspiring learning. With this article, we will share some of our principles of inspiring learning as well as give examples about how to do it in practice. Principles are connected to the powerful relationship between student and teacher, using natural environments as part of learning, providing possibilities for personalized learning, connecting learning to a story that has purpose and having fun when learning. Teachers should focus to empower students to learn, instead of teaching them. To learn is the most important competence to learn and teachers should provide possibilities for students to focus on why, instead of focusing on how or what lo learn.